Does digital technology service foster income gains in rural villages? Evidence from China’s third agricultural census - Zhong, Shunbin; Shen, Weiteng; Yang, Peng (Frontiers in Sustainable Food Systems, 2024)
The application of digital technology service like rural e-commerce service centers (RESCs) has captured considerable attention in China, but existing literature has not yet provided solid empirical evidence regarding its potential to foster rural income gains. Utilizing large-scale survey data from the Third National Agricultural Census (TNAC) of China, this study attempts to investigate the impact and underlying mechanisms of RESCs on income gains across 49,135 villages. The results indicate that RESCs significantly increase village income gains in rural China, which confirm the theory of “space of flows.” In addition, heterogeneity analysis reveals that this income increasing effect is significantly higher in eastern China, as well as in rural villages with migrant populations and college-graduate cadres. The conclusion remains robust even after conducting several robustness checks and instrumental variable estimation. Furthermore, mechanism analysis unveils that RESCs improve village income gains by promoting characteristic agricultural development, encouraging entrepreneurship, and enhancing government funding support. The findings shed light on policy implications for the design and implementation of rural digital technology policies in developing countries.